First record of the genus Aplomerus Provancher, 1886 (Hymenoptera: Ichneumonidae: Xoridinae) from the Oriental region, with descriptions of two new species - Varga, Oleksandr; Reshchikov, Aleksey; Broad, Gavin R. (Zootaxa, 2014)
The genus Aplomerus Provancher, 1886 (Hymenoptera, Ichneumonidae) is a small genus of the subfamily Xoridinae. Two new species from Asia, A. orientalis Varga & Reshchikov sp. n. from Thailand and A. phamae Broad sp. n. from Vietnam, are described and illustrated. An identification key for Asian species is provided. These are the first records of the genus from the Oriental region and increases the known number of Aplomerus species to eight, with a disjunct distribution of North America, Japan and south-east Asia.